PENGEMBANGAN MODEL LATIHAN STRATEGI SERANGAN DALAM PERMAINAN FUTSAL ( Studi pada Pemain Futsal Putra Tingkat Intermediate di Kota Pontianak ) - Daryanto, Zusyah Porja (IKIP PGRI Pontianak, 2013)
The purposes of this research are; (1) to organize a training program of a good attack training, (2) the implementation of try out practice model to improve the attack ability of male futsal player in intermediate level in Pontianak effectively and efficiently, (3) to find out the result of effectiveness test training model in improving the ability of attacking to male futsal player in intermediate level. The method of this research is Research and Development. The technique of data collecting was using interview, questionnaires, test and observation. The result finding of evaluation data from the experts is 71.31%. The result finding of limited try out is 68.32%. The result finding of expansive try out is 82.04% and it was interpreted that the product design of attacking training model development to intermediate level can be tested to the effectiveness test stage. The result of effectiveness test product by comparing two groups; treatment group which using development product, and control group which using pretest and posttest design. Mean score of each group based on the test is the effectiveness of experiment group is higher than the control group. The effectiveness score of control group is 65.6% and experiment group is 84.4%. The player rotation in control group is 62.5% and experiment group is 87.5%. The movement without ball in control group is 62.5% and in experimental group is 87.5%. The ball control in control group is 75% and experiment group is 87.5%. Team work in control group is 62.5% and expreiment group is 75%. Based on the data above it can be seen that the training by using attacking strategy training model in playing futsal can increase the player rotation from 62.5% into 87.5%, the ball control from 75% into 87.5% and team work from 62.5% into 75%. Based on the comparison of those test results, the improvement of test result for the expreiment group is incresing significantly than in the control group. The last was obtained after the training program was implemented to each group. In conclusion, the product is profoundly effective in improving the player ability in attacking strategy.Â Keywords: Futsal, Development, Model, Training, Attacking Strategy